What different physical techniques can disclose about disruptions on membrane structure caused by the antimicrobial peptide Hylin a1 and a more positively charged analogue - Vignoli Muniz, Gabriel S.; Duarte, Evandro L.; Lorenzón, Esteban N.; Cilli, Eduardo M. [UNESP]; Lamy, M. Teresa (Elsevier, 2022)
The present work monitors structural changes in anionic membranes (DPPG; 1,2-dipalmitoyl-sn-glycero-3-phospho-(1′-rac-glycerol)) caused by the native antimicrobial peptide (AMP) Hylin a1 (Hya1; IFGAILPLALGALKNLIK-NH2) and its synthetic analogue K0Hya1 (KIFGAILPLALGALKNLIK-NH2), with an extra positive residue of lysine at the N-terminus of the peptide chain. Anionic membranes were used to mimic anionic lipids in bacteria membranes. Differential scanning calorimetry (DSC) evinced that both peptides strongly disrupt the lipid bilayers. However, whereas the native peptide (+3) induces a space-average and/or time-average disruption on DPPG bilayers, the more charged, K0Hya1 (+4), appears to be strongly attached to the membrane, clearly giving rise to the coexistence of two different lipid regions, one depleted of peptide and another one peptide-disrupted. The membrane fluorescent probe Laurdan indicates that, in average, the peptides increase the bilayer packing of fluid DPPG (above the lipid gel-fluid transition temperature) and/or decrease its polarity. Spin labels, incorporated into DPPG membrane, confirm, and extend the results obtained with Laurdan, indicating that the peptides increase the lipid packing both in gel and fluid DPPG bilayers. Therefore, our results confirm that Laurdan is often unable to monitor structural modifications induced on gel membranes by exogenous molecules. Through the measurement of the leakage of entrapped carboxyfluorescein (CF), a fluorescent dye, in DPPG large unilamellar vesicles it was possible to show that both peptides induce pore formation in DPPG bilayers. Furthermore, CF experiments show that Hylin peptides are strongly bound to DPPG bilayers in the gel phase, not being able to migrate to other DPPG vesicles. Here we discuss the complementarity of different techniques in monitoring structural alterations caused on lipid bilayers by Hylin peptides, and how it could be used to help in the understanding of the action of other exogenous molecules on biological membranes.
Keywords: Antimicrobial peptide; Carboxyfluorescein assay; Differential Scanning Calorimetry; Laurdan; Liposomes; Spin label